2022
DOI: 10.3390/ma15196755
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Microstructures and High-Temperature Oxidation Resistance of Cr Coatings on Zircaloy-4 by Multi-Arc Ion Plating Technology

Abstract: Introducing the oxidation-resistant coating on Zr alloy is considered to be one of the potential solutions for accident-tolerant fuel (ATF) materials. In this study, pure Cr coatings were prepared on a Zircaloy-4 (Zry-4) alloy surface by multi-arc ion plating under different process parameters. The ability of Cr coating on Zry-4 alloy cladding to improve the oxidation resistance to prevent a loss-of-coolant accident (LOCA) was studied. The microstructure of Cr coating was analyzed using the EBSD technique, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Many researchers have paid much attention to the studies of the preparation process, high-temperature oxidation performance, and radiation resistance of Cr coating on the surface of zirconium alloy cladding. [21][22][23][24][25][26][27] Among various deposition technologies, multi-arc ion plating seems to be the most suitable technology for the coating preparation on the surface of cladding materials, due to its high ionization degree, high deposition rate, strong coating/substrate, and so forth. [28,29] For example, He et al [30] reported that the Cr 2 O 3 formed during oxidation at 1060°C on the surface of Cr coating prepared by the multi-arc ion plating technique caused a reduction in the weight gain of Zircaloy by 93.35%.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have paid much attention to the studies of the preparation process, high-temperature oxidation performance, and radiation resistance of Cr coating on the surface of zirconium alloy cladding. [21][22][23][24][25][26][27] Among various deposition technologies, multi-arc ion plating seems to be the most suitable technology for the coating preparation on the surface of cladding materials, due to its high ionization degree, high deposition rate, strong coating/substrate, and so forth. [28,29] For example, He et al [30] reported that the Cr 2 O 3 formed during oxidation at 1060°C on the surface of Cr coating prepared by the multi-arc ion plating technique caused a reduction in the weight gain of Zircaloy by 93.35%.…”
Section: Introductionmentioning
confidence: 99%